Modernization and tradition in the Western Sahara, the Sahrawi Constitution - Jorge Gamaliel Arenas Basurto, Claudia Barona Castañeda e (Africana Studia, 2020)
Countries in the Middle East and North Africa experienced, like many other former colonies, an imposition of a Western concept of Modernization that clashed with their traditions and produced complex networks of discrepancies in their political apparatus. The Sahrawi experience is no different from the abovementioned. With particular characteristics such as its historical background of exile, a humanitarian need for relief, and its position in the region, this dispute between tradition and modernity is all the more evident in a State that seeks international recognition. Due to these factors, the Sahrawi state was drove to build its political system abruptly. A literature review will trace the structural changes where tradition and modernization appear in the implementation of a legal framework. With the goal to understand the development of the Sahrawi State political machinery, core texts such as the Five Constitution Acts and the Provisional Constitution Act of 1976 ought to be considered. At the same time, this paper argues that the process of modernization carried out by the Sahrawi State comes out as an unsuccessful attempt to separate itself from its rooted tribal traditions. This has raised numerous contradictions in the law together with the creation of a State that may come off as weak and corruption-prone. This paper is part of the Laboratory of Islamic Studies at Universidad de las Americas Puebla in Mexico. Keywords: Sahrawi, Constitution, Islam, State.